Cryo Assisted Minimally Invasive Surgery for the Treatment of Orbital Cavernous Haemangiomas - Janjua Omer Farooq, Muhammad Amer Yaqub, Saadullah Ahmad, Muhammad Khizar Niazi Teyyeb Azeem (Pakistan Journal of Ophthalmology, 2018)
Purpose: To study cryo assisted minimally invasive surgery for the treatment of orbital cavernous hemangiomas. Material and Methods: We present a case series of six patients having orbital cavernous haemangiomas. All patients underwent minimally invasive cryosurgical extraction of the tumour at the Armed Forces institute of Ophthalmology, Rawalpindi. Results: All the tumours were successfully removed en bloc with the help of cryo extraction. The vision was improved in all but one case. The recovery was uneventful and histopathological reports confirmed the diagnosis after more follow-ups of nine months, no recurrence was observed in any of the operated eye. Conclusion: Cryo-assisted minimally invasive surgery offers an exciting approach for management orbital cavernous hemangiomas, with good cosmetic results and early functional recovery.